Transactional Justice and Customer Satisfaction in Cafés: An Islamic Ethical Perspective: An Islamic Ethical Perspective - Adib Susilo; Iqbal Imari; Rahmad Hakim; Atha Mahdi Muhammad (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to investigate the determinants of customer satisfaction in the café industry by analyzing the relationships between product and service quality, promotion, hospitality, price perception, and satisfaction. Furthermore, it seeks to interpret these marketing dynamics through the lens of Islamic commercial ethics to understand the ethical foundations of consumer exchange. Design/methodology/approach – A quantitative approach was employed using a survey of 124 café customers in Indonesia. The data were analyzed through a two-stage approach: Exploratory Factor Analysis (EFA) to identify underlying constructs, followed by Structural Equation Modeling (SEM) to validate the measurement model and test the structural hypotheses. The model's validity was confirmed through Confirmatory Factor Analysis (CFA). Finding/Results – The results indicate that product and service quality significantly influence price perception, which in turn significantly dictates customer satisfaction. Conversely, promotion and hospitality do not significantly affect price perception. The findings reveal that satisfaction is primarily shaped by value congruence and transactional justice. From an Islamic ethical perspective, satisfaction emerges when there is just equivalence (ʿadl) and mutual consent (ridha) regarding the price-value exchange, while hospitality acts as benevolence (ihsan) that complements but does not determine economic valuation. Originality/Value – This study contributes to the literature by linking perceived price fairness with Islamic commercial ethics (ʿadl, ridha, and ihsan). It shifts the understanding of customer satisfaction from a purely emotional or persuasive marketing outcome to an ethical approval of exchange grounded in transactional justice. The study is limited by its specific focus on the café industry and a relatively small sample size drawn through convenience sampling, which may affect generalizability. Future research should involve a larger, more diverse demographic and consider longitudinal data to observe changes in ethical consumption patterns over time.